How to get by in a floodplain forest: the reaction to forestry as evidenced by the Tawny owl Strix aluco (Avocetta, 2016)
To establish a management plan that does not contribute to species loss, it is essential to fully understand the response by organisms to human impacts. Forests on floodplain of rivers face several threats. One of them is intensive forestry. Along the Danube River, forests are changing rapidly, which affects the composition of species. Due to short rotation logging, cavity-nesting birds are restricted by the lack of old trees. Thus, in our study we intended to identify the habitat preferences of the Tawny Owl, in areas with populous plantations and fragments of natural softwood forest. We measured 28 environmental parameters (type of forest, age, perimeter of trees, height and coverage of herbaceous layer, shrub and trees in proper categories) in Tawny owl territories as well as outside these territories. By using discriminant analysis with forward stepwise method we found significant difference in overall vegetation structure inside and outside the territories. The Tawny owl remains close to the oldest (older than 26 years) and largest trees (with perimeter greater than 161 cm), which are common for patches of natural forest. However, the owl seems to avoid monocultures with small trees and larger cover of tall grass and shrubs. Hence we concluded that the natural forests should be maintained as a fundamental element in the floodplain areas. Furthermore, based on our results, the priority of managing the populous plantations should be in a way that at least few old trees would remain in logging units.
Keywords: floodplain forest; Tawny Owl; habitat preference